2012
DOI: 10.1590/s0100-204x2012000100013
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of productivity and polysaccharide-protein complex in Agaricus blazei

Abstract: -The objective of this work was to assess the productivity and polysaccharide-protein complex content of Agaricus blazei on rice straw medium, in comparison to conventional sawdust, using four casing soils. The A. blazei strain used was BCRC36814 T , purchased from the Food Industry Research and Development Institute, Hsin-Chu, Taiwan. The two media were evaluated as to A. blazei productivity, harvesting time, and production costs. The experimental design used was a randomized complete block, with four replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Harvesting time of the fruiting body took place when the mushroom reached its highest biomass, which occurs during the immature stage, when the veil membrane is enclosed and the gills are intact (Mendonça et al, 2005;Pokhrel & Ohga, 2007;Chu et al, 2012). Total mushroom fresh yield (g per pot) and PSPC content were measured from the first mushroom flush.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Harvesting time of the fruiting body took place when the mushroom reached its highest biomass, which occurs during the immature stage, when the veil membrane is enclosed and the gills are intact (Mendonça et al, 2005;Pokhrel & Ohga, 2007;Chu et al, 2012). Total mushroom fresh yield (g per pot) and PSPC content were measured from the first mushroom flush.…”
Section: Methodsmentioning
confidence: 99%
“…Pharmacological studies have shown that bioactive substances, such as polysaccharide-protein complexes (PSPC) from A. blazei, function as antioxidants, antimutagenics, antitumorigenics, and anticancer agents (Kimura et al, 2004;Firenzuoli et al, 2008). However, the harvesting time of A. blazei is relatively long (approximately 60 days) when compared to other related Agaricus sp., including A. bisporus (approximately 30 days) (Pardo-Gimenez et al, 2010;Chu et al, 2012). Attempts to improve A. blazei productivity have mainly focused on the application of different combinations of culture media and casing soils (Pardo-Gimenez et al, 2010;Chu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional culturing of ABM requires the initial spawning of the mycelium on a solid culture medium (15 to 21 days), and subsequent covering with suitable casing soil to stimulate fruiting-body formation, which normally takes around 45 to 60 days (Colauto et al, 2010;Chu et al, 2012). The time required to culture ABM from spawning to a harvestable mushroom size is long, compared to related Agaricus sp., such as A. bisporus (25 to 35 days, Pardo-Gimenez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…bras., Brasília, v.47, n.6, p.815-821, jun. 2012 energy supply -for ABM cultures are often in the range of 40-70% (Mendonça et al, 2005;Donini et al, 2006;Andrade et al, 2007;Pokhrel & Ohga, 2007;Colauto et al, 2010;Chu et al, 2012). As such, it would be beneficial to identify techniques to decrease the time and energy required to culture ABM.…”
Section: Introductionmentioning
confidence: 99%